Implementation Of Training Aid Tools Development (Remote Control and Headset) For Sprint Tunanetra Athletes - Albadi Sinulingga; Novita Novita; Joni Tohap Maruli Nababan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to develop training aids (remote control and headset) for sprint athletes with visual impairments as a directional controller during a sprint running exercise program. The benefit of this research is to produce training aids for sprint athletes with visual impairments. This study uses research and development research and development methods. The research was carried out in 2 places, namely the Yapentra SLB-A school for small-scale trials and Karya Murni's SLB-A large-scale trials for the development of blind sprint athletes in North Sumatra NPC. The analysis technique uses quantitative descriptive. The conclusions of this study are: (1) In using remote control and headsets, athletes focus more on personal abilities without thinking about collaboration, acceleration and communication, (2) Using remote control and headsets, athletes are more confident and more independent in sprinting activities. Using remote control and headsets, guades and coaches are more focused in conveying information and are more efficient in training blind athletes with sprint running numbers by looking at personal abilities and motivation as sprint athletes running norms.